Community structure and biomass of reef fish concerning coral cover in Sempu Strait, East Java, Indonesia - ANDIK ISDIANTO; MUHAMMAD FIKRI ARIEFANDI; MUHAMMAD ARIF ASADI; ADE YAMINDAGO; FAHREZA OKTA SETYAWAN; GATUT BINTORO; ARIEF SETYANTO; TRI DJOKO LELONO; AGUS TUMULYADI; WIRASTIKA ADHIHAPSARI; DESY SETYONINGRUM; AULIA LANUDIA FATHAH; BERLANIA MAHARDIKA PUTRI; SUPRIYADI SUPRIYADI; OKTIYAS MUZAKY LUTHFI (Society for Indonesian Biodiversity, 2024)
Abstract. Isdianto A, Ariefandi MF, Asadi MA, Yamindago A, Setyawan FO, Bintoro G, Setyanto A, Lelono TD, Tumulyadi A, Adhihapsari W, Setyoningrum D, Fathah AL, Putri BM, Supriyadi, Luthfi OM. 2024. Community structure and biomass of reef fish concerning coral cover in Sempu Strait, East Java, Indonesia. Biodiversitas 25: 3376-3385. Reef fishes were used as bioindicators of biodiversity in coral reef ecosystems. However, coral cover and reef fish abundance around Sempu Strait tended to decrease. The study aims to obtain reef fish's community structure and biomass and their correlation to coral cover. We observed significant variability in reef fish populations through bi-monthly monitoring using an underwater visual census and underwater photo transect conducted from December 2022 to April 2023. Based on these observations, the average range of coral fish abundance was 0.453 to 0.577 individuals per square meter, with the highest value at Rumah Apung station (0.577 ind/m2). The community structure included 81 reef fish species, categorized into major (50 species), indicator (10 species), and target (21 species) groups, demonstrating a community with moderate diversity, stable evenness, and low dominance across the observed stations. Further, the research quantified fish biomass, recording an average of 0.0207 kg/m2 or 207.571 kg/Ha, categorized as low, with the highest biomass measurements at Rumah Apung station (0.0054 kg/m2). Strong correlations were identified between coral cover and both fish abundance (correlation coefficient = 0.741) and biomass (correlation coefficient = 0.666). These results emphasize the profound impact of coral health on the conditions and sustainability of reef fish populations. These findings underscore the critical dependency of reef fish on coral ecosystems and provide essential data for conservation efforts to maintain and restore these vital marine habitats.